Is fatigue a necessary requirement for adaptation to a strength training program? - Chickonoski, T. (1997)
In summary, fatigue consists of central, peripheral and biochemical components which can in isolation on in combination determine the level of performance of any athlete. Fatigue is a necessary requirement for a strength training program to produce over compensation and raise the threshold for the effects of fatigue during competition. Recovery is an essential component to prevent adverse effects of fatigue and to avoid the pathological conditions of overtraining.